2022
DOI: 10.1021/acs.biomac.2c01062
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Stimulation of Self-Assembly Tunes the Elastic Properties of Interpenetrated Biosurfactant–Biopolymer Hydrogels

Abstract: Hydrogels are widespread soft materials, which can be used in a wide range of applications. The control over the viscoelastic properties of the gel is of paramount importance. Ongoing environmental issues have raised the consumer's concern toward the use of more sustainable materials, including hydrogels. However, are greener materials compatible with high functionality? In a safe-by-design approach, this work demonstrates that functional hydrogels with in situ responsivity of their elastic properties by exter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 67 publications
(195 reference statements)
1
4
0
Order By: Relevance
“…The addition of vesicles (pH < 7) or micelles (pH > 7) to the biopolymer hydrogel resulted in a gel with slightly lower mechanical strength. These observations seem to be generalized to all the biopolymers tested here and could be reproduced under non-equilibrium conditions by means of pH-resolved in situ SAXS experiments …”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The addition of vesicles (pH < 7) or micelles (pH > 7) to the biopolymer hydrogel resulted in a gel with slightly lower mechanical strength. These observations seem to be generalized to all the biopolymers tested here and could be reproduced under non-equilibrium conditions by means of pH-resolved in situ SAXS experiments …”
Section: Discussionsupporting
confidence: 59%
“…These observations seem to be generalized to all the biopolymers tested here and could be reproduced under non-equilibrium conditions by means of pH-resolved in situ SAXS experiments. 64 Both the increase and decrease of mechanical properties were tentatively explained through the possible evolution of the biopolymer's mesh size. Despite the fact that the SAXS data did not reach a plateau at low q-values, which was necessary to quantify the mesh size, the OZ plots suggested that the insertion of micelles contributed to increasing the mesh size of the biopolymer hydrogel, while the fibers interpenetrated the biopolymer gel without specific interactions.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…This mechanism facilitates the removal of cobalt (up to 95%) and significant percentages for other metals, including Cu 2+ , Ni 2+ , and Cr 2+ . , Additionally, they successfully developed interpenetrated hydrogels composed of biosurfactant and biopolymer by utilizing biobased glycolipid amphiphiles and biopolymers. This highlights the feasibility of creating functional hydrogels with elastic properties that respond in situ to external stimuli, all derived from entirely sustainable components …”
Section: Glycolipid-based Gelatorsmentioning
confidence: 99%
“…This highlights the feasibility of creating functional hydrogels with elastic properties that respond in situ to external stimuli, all derived from entirely sustainable components. 84 Four efficient LMWGs are reported from the cholesterol and sugar components. Gelation experiments conducted in different solvents revealed that even a slight modification in the linker length could result in a significant alteration in the gelation characteristics and properties of the compounds.…”
Section: Glycolipid Gelatorsmentioning
confidence: 99%
“…Amphiphilic molecules have been used as surfactants to stabilize hydrophobic and hydrophilic polymers in hydrogels. 6–10 By contrast, mixtures of amphiphilic monomer, hydrophobic polymer, and water have rarely been studied. 5,11 Polymerization of the amphiphilic monomer has been shown to lead to hydrogels of unusual properties.…”
Section: Introductionmentioning
confidence: 99%